EARLY CHILHOOD SELF-CONCEPT RELATED TO PROSOCIAL BEHAVIOR - Sitepu, Juli Maini (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to see the relationship between early childhood self-concept and prosocial behavior. The research method used is a literature study from several books, journals and information obtained from the internet and print media. The results of the literature study show that the development of self-concept in early childhood is basically influenced by the family environment, school environment, play environment and the surrounding environment. Self-concept and prosocial behavior influence each other, where self-concept is formed by the child's social behavior and conversely the child's prosocial behavior is strongly influenced by the child's self-concept.